The Diaries of Emperor Charles VI: “Sneak Peeks” into the Daily Routine of the Imperial Viennese Court - Stefan Seitschek (Royal Studies Journal, 2021)
Between 1707 and 1740, the Holy Roman Emperor, Archduke Charles VI of Austria (1685–1740), maintained a near-continuous diary, recording his personal reflections on more than thirty years of rule. This article analyses these insights into Charles’s daily life within the wider context of the Habsburg monarchy and the imperial court during the early eighteenth century, illuminating the ruler’s perspective on familial relationships, annual ceremonies, diplomatic endeavours, and decision-making processes. First, the nature of these records and their positioning within the wider context of diary culture is considered, as well as the distinctive features of Charles’s entries and the challenges inherent in deciphering them. The article then investigates Charles’s personal piety, his relationship with his family, and his various advisors at the Viennese court, as demonstrated by his diary entries during his rule. Combining diplomatic, political, and private contemplations, and offering valuable details about the monarch’s day-today routine, this study presents Charles’s diaries as an intimate and essential record of the Baroque period, as well as a unique set of records that reveal the Archduke-Emperor’s innermost thoughts.